sCD163 levels as a biomarker of disease severity in leprosy and visceral leishmaniasis. - Ricardo Luís Louzada Silva; Marcio B Santos; Priscila L S Almeida; Thayse S Barros; Lucas Magalhães; Rodrigo A Cazzaniga; Patrícia R M Souza; Nívea F Luz; Jaqueline França-Costa; Valeria M Borges; Djalma S Lima-Junior; Michael W Lipscomb; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:CD163, receptor for the haptoglobin-hemoglobin complex, is expressed on monocytes/macrophages and neutrophils. A soluble form of CD163 (sCD163) has been associated with the M2 macrophage phenotype, and M2 macrophages have been shown to down-modulate inflammatory responses. In particular, previous studies have shown that M2 is closely associated with the most severe clinical presentation of leprosy (i.e. lepromatous leprosy (LL)), as well as tuberculosis. We hypothesized that sCD163 correlates with severity of diseases caused by intracellular pathogens. METHODOLOGY/PRINCIPAL FINDINGS:To assess this hypothesis, sCD163 levels were measured in the serum of leprosy and visceral leishmaniasis (VL) patients stratified by severity of the clinical presentation. sCD163 levels were significantly higher in patients with these diseases than those observed in healthy control individuals. Further analyses on infection and disease status of leprosy and VL patients revealed a clear association of sCD163 levels with clinical parameters of disease severity. In vitro culture assays revealed that Leishmania infection induced CD163 expression on the surface of both monocyte/macrophages and neutrophils, suggesting these cells as possible sources of sCD163. FACS analyses shows that the cells expressing CD163 produces both TNF-α and IL-4. CONCLUSIONS/SIGNIFICANCE:Taken together, our results reveal sCD163 as a potential biomarker of severity of diseases caused by intracellular pathogens M. leprae and Leishmania spp. and have a modulatory role, with a mix of an inflammatory property induced by TNF-α release, but that potentially induces an anti-inflammatory T cell response, related to IL-4 release.